Career Mentoring Needs of Youths in Foster Care: Voices for Change. Issue 2 (23rd April 2013) - Hudson, Angela L.
<x xml:space="preserve">Abstract</x> Problem Adolescents with a history of foster care placement are more likely to become homeless, have mental illness, become parents too early in life, or become incarcerated within the juvenile justice/prison system. In addition, a low percentage of young adults, who formerly were in foster care, complete vocational training or higher education. Methods This was a qualitative study, using focus group methodology. Four focus group sessions were conducted with youth living in foster care. The purpose was to obtain their perceptions about mentoring. Focus groups comprised six to eight youths per group and were guided by a semi‐structured interview guide. Findings A total of 27 youth in foster care participated in focus group interviews. Mean age was 16.4 (SD = 0.68) years. Youth participants were very knowledgeable about mentoring programs for at‐risk youth, along with negative psychosocial outcomes experienced by former foster youth. However, they remarked that they are given few opportunities for career mentoring. The overall themes that emerged from narrative data were needing and finding authority figures, hooking up with a career mentor, and deserving the good life. Conclusion Career mentoring is an affordable and feasible intervention for child welfare agencies. This could lead to more motivated and prepared youth living in foster care for vocational training or higher education. Learning opportunities from a career mentor may be a lifeline for preventing negative psychosocial outcomes for foster youth, reward achievement goals, and improve overall quality of life in emerging adulthood.